Optimization of the doxycycline-dependent simian immunodeficiency virus through in vitro evolution - Piatak Mike; Yuan Fang; Almond Neil; Page Mark; Ooms Marcel; Harwig Alex; Centlivre Mireille; Klaver Bep; Das Atze T; Lifson Jeffrey D; Berkhout Ben (Retrovirology, 2008)
Abstract Background Vaccination of macaques with live attenuated simian immunodeficiency virus (SIV) provides significant protection against the wild-type virus. The use of a live attenuated human immunodeficiency virus (HIV) as AIDS vaccine in humans is however considered unsafe because of the risk that the attenuated virus may accumulate genetic changes during persistence and evolve to a pathogenic variant. We earlier presented a conditionally live HIV-1 variant that replicates exclusively in the presence of doxycycline (dox). Replication of this vaccine strain can be limited to the time that is needed to provide full protection through transient dox administration. Since the effectiveness and safety of such a conditionally live virus vaccine should be tested in macaques, we constructed a similar dox-dependent SIV variant. The Tat-TAR transcription control mechanism in this virus was inactivated through mutation and functionally replaced by the dox-inducible Tet-On regulatory system. This SIV-rtTA variant replicated in a dox-dependent manner in T cell lines, but not as efficiently as the parental SIVmac239 strain. Since macaque studies will likely require an efficiently replicating variant, we set out to optimize SIV-rtTA through in vitro viral evolution. Results Upon long-term culturing of SIV-rtTA, additional nucleotide substitutions were observed in TAR that affect the structure of this RNA element but that do not restore Tat binding. We demonstrate that the bulge and loop mutations that we had introduced in the TAR element of SIV-rtTA to inactivate the Tat-TAR mechanism, shifted the equilibrium between two alternative conformations of TAR. The additional TAR mutations observed in the evolved variants partially or completely restored this equilibrium, which suggests that the balance between the two TAR conformations is important for efficient viral replication. Moreover, SIV-rtTA acquired mutations in the U3 promoter region. We demonstrate that these TAR and U3 changes improve viral replication in T-cell lines and macaque peripheral blood mononuclear cells (PBMC) but do not affect dox-control. Conclusion The dox-dependent SIV-rtTA variant was optimized by viral evolution, yielding variants that can be used to test the conditionally live virus vaccine approach and as a tool in SIV biology studies and vaccine research.